Combination Therapy With Rapamycin and Low Dose Imatinib in Pulmonary Hypertension - Shi, Yinan; Gu, Chenxin; Zhao, Tongtong; Jia, Yangfan; Bao, Changlei; Luo, Ang; Guo, Qiang; Han, Ying; Wang, Jian; Black, Stephen M.; Desai, Ankit A.; Tang, Haiyang (Frontiers in Pharmacology, 2021)
Rationale: Enhanced proliferation and distal migration of human pulmonary arterial smooth muscle cells (hPASMCs) both contribute to the progressive increases in pulmonary vascular remodeling and resistance in pulmonary arterial hypertension (PAH). Our previous studies revealed that Rictor deletion, to disrupt mTOR Complex 2 (mTORC2), over longer periods result in a paradoxical rise in platelet-derived growth factor receptor (PDGFR) expression in hPASMCs. Thus, the purpose of this study was to evaluate the role of combination therapy targeting both mTOR signaling with PDGFR inhibition to attenuate PAH development and progression. Methods and Results: Immunoblotting analyses revealed that short-term exposure to rapamycin (6h) significantly reduced phosphorylation of p70S6K (mTORC1-specific) in hPASMCs but had no effect on the phosphorylation of AKT (p-AKT S473, considered mTORC2-specific). In contrast, longer rapamycin exposure (>24h), resulted in differential AKT (T308) and AKT (S473) phosphorylation with increases in phosphorylation of AKT at T308 and decreased phosphorylation at S473. Phosphorylation of both PDGFRɑ and PDGFRβ was increased in hPASMC after treatment with rapamycin for 48h and 72h. Based on co-immunoprecipitation studies, longer exposure to rapamycin (24-72h) significantly inhibited the binding of mTOR to Rictor, mechanistically suggesting mTORC2 inhibition by rapamycin. Combined exposure to longer-term rapamycin with the PDGFR inhibition, imatinib significantly reduced the proliferation and migration of hPASMCs compared to either agent alone. Pre-clinical studies validated increased therapeutic efficacy of rapamycin combined with imatinib in attenuating PAH over either drug alone. Specifically, combination therapy further attenuated pulmonary hypertension (PH) development in both monocrotaline (MCT) and Hypoxia/Sugen rats as demonstrated by further reductions in the Fulton index, right ventricular systolic pressure (RVSP), pulmonary vascular wall thickness and vessel muscularization, and decreased proliferating cell nuclear antigen (PCNA) staining in PASMCs. Conclusion: Prolonged rapamycin treatment activates PDGFR signaling, in part, via mTORC2 inhibition. Combination therapy with rapamycin and imatinib may be a more effective strategy for the treatment of PAH.